Privacy vs. Security - Stalla-Bourdillon, Sophie; Phillips, Joshua; Ryan, Mark D. (SpringerBriefs in Cybersecurity,, 2014)
Securing privacy in the current environment is one of the great challenges of today's democracies. Privacy vs. Security explores the issues of privacy and security and their complicated interplay, from a legal and a technical point of view. Sophie Stalla-Bourdillon provides a thorough account of the legal underpinnings of the European approach to privacy and examines their implementation through privacy, data protection and data retention laws. Joshua Philips and Mark D. Ryan focus on the technological aspects of privacy, in particular, on today's attacks on privacy by the simple use of today's technology, like web services and e-payment technologies and by State-level surveillance activities.